Struggle for Customary Rights and State Certification: Problems of Customary Land Grants - Widyana Mareta Anwar; Nur Mohamad Kasim; Erman I. Rahim (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
overlapping conflict between customary land grants and land ownership certificates is a serious problem in the Indonesian land law system, reflecting the tension between customary law based on social-communal recognition and positive law oriented towards administrative certainty. This study uses a descriptive-analytical normative juridical approach through a literature review of the 1945 Constitution Articles 18B and 33, the 1960 UUPA Articles 3 and 5, Government Regulation 24/1997, and the Constitutional Court decisions 35/PUU-X/2012 and 1012 K/Pdt/2023, combined with an analysis of empirical data on customary land grant cases in Central Kalimantan, Tana Toraja, East Manggarai, Sorong, and Baduy (2020-2024). The findings indicate that land ownership certificates have superior legal force in judicial practice due to the presumption of regularity mechanism, but are not immune to correction because Government Regulation 24/1997 allows for proof of conversion of old rights through non-formal evidence. Harmonization of customary law and positive law requires: first, recognition of customary evidence as prima facie evidence in land administration; second, strengthening coordination between the National Land Agency (BPN), the Regional Government (Pemda), and Customary Institutions; third, development of a restorative mediation mechanism that integrates customary leaders and district courts; fourth, reform of customary land registration policies and customary law literacy. This study concludes that substantive justice for indigenous communities can be achieved through operational legal pluralism without sacrificing legal certainty, by protecting customary rights as an integral part of the nation's cultural heritage that deserves to be respected and consistently protected in every aspect of national land policy.